Empowering students for economic self-sufficiency: insights into entrepreneurial education - Elgharbawy, Amal A.M.; Yuhan, Avicenna; Kotachi, Mariam; Schianchi, Martina (Springer Nature, 2025)
As graduating students transition into the professional world, they often find that their college education did not teach them the skills businesses demand. This disconnect between the skills learned during college and the skills needed to succeed within the workforce has led to increasing levels of unemployment and underemployment. Implementing entrepreneurial education in colleges could resolve many of the skill deficiencies both at the undergraduate and graduate levels. By training students entrepreneurial skills, colleges empower these students to think beyond conventional boundaries and develop productive economic activities. This paper reviews the positive impacts of entrepreneurial education in shaping the next generation of workers while also delving into theoretical frameworks, such as human capital and social cognitive theories, to understand the reasoning behind the success of entrepreneurial education. This research further addresses the steps and requirements for a successful implementation, the role of technology in the implementation process, and possible challenges faced which might impede on effective implementation.